Active steering system based on nonlinear control system - Mohd. Isira, Ahmad Sadhiqin (2007)
The objective of this project is to improve the performance of steering control of a vehicle. This can be achieved by designing a nonlinear active steering control system which will compensate disturbances such as road conditions and crosswind. The model of the system is derived and simulated based on the single track car model which has been established as a basis of any car steering system. A nonlinear active steering controller is then be designed by using the Sliding Mode Control (SMC) strategy whereby yaw rate and side slip angle are used as the control parameters. The proposed controller is applied to the nonlinear system, simulated and tuned using Matlab/Simulink platform. Yaw rate, side slip angle, control inputs and sigmas are considered as the parameters that contribute to the performance of the proposed controller. Performance of the developed controller is then being compared to the performance of Linear Quadratic Regulator (LQR) and pole placement controller to verify its robustness and stability.